Korea : Selected Issues. (IMF Staff Country Reports; Country Report ;, 1998)
This Selected Issues paper analyzes corporate restructuring and corporate governance in the Republic of Korea. The paper describes the chaebols and their role in the economy. It reviews the government's role in shaping and regulating the chaebols, explains factors that have encouraged debt over equity finance, and describes the key elements in corporate governance. Weaknesses in the Korean corporate governance system are described. The paper also discusses the reforms to strengthen the Korean corporate governance system and to promote corporate restructuring.